Mn2+ bispidine complex combining exceptional stability, inertness, and MRI efficiency - Ndiaye, Daouda; Cieslik, Patrick; Wadepohl, Hubert; Pallier, Agnès; Même, Sandra; Comba, Peter; Jakab-Tóth, Éva (Journal of the American Chemical Society, 2022)
As an essential metal ion and an efficient relaxation agent, Mn2+ holds a great promise to replace Gd3+ in magnetic resonance imaging (MRI) contrast agent applications, if its stable and inert complexation can be achieved. Toward this goal, four pyridine and one carboxylate pendants have been introduced in coordinating positions on the bispidine platform to yield ligand L3. Thanks to its rigid and preorganized structure and perfect size match for Mn2+, L3 provides remarkably high thermodynamic stability (log KMnL = 19.47), selectivity over the major biological competitor Zn2+ (log(KMnL/KZnL) = 4.4), and kinetic inertness. Solid-state X-ray data show that [MnL3(MeOH)](OTf)2 has an unusual eight-coordinate structure with a coordinated solvent molecule, in contrast to the six-coordinate structure of [ZnL3](OTf), underlining that the coordination cavity is perfectly adapted for Mn2+, while it is too large for Zn2+. In aqueous solution, 17O NMR data evidence one inner sphere water and dissociatively activated water exchange (kex298 = 13.5 × 107 s-1) for MnL3. Its water proton relaxivity (r1 = 4.44 mM-1 s-1 at 25 °C, 20 MHz) is about 30% higher than values for typical monohydrated Mn2+ complexes, which is related to its larger molecular size; its relaxation efficiency is similar to that of clinically used Gd3+-based agents. In vivo MRI experiments realized in control mice at 0.02 mmol/kg injected dose indicate good signal enhancement in the kidneys and fast renal clearance. Taken together, MnL3 is the first chelate that combines such excellent stability, selectivity, inertness and relaxation properties, all of primary importance for MRI use.
Im Titel ist "2+" hochgestellt
Published online29 November 2022
Gesehen am 08.02.2023